Sistem Informasi Administrasi di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumba Barat Daya - Alfons Umbu Awang; Adelbertus Umbu Jangga; Alexander Talo Popo (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
The increasing population growth with uneven distribution and low population quality has become a problem related to population in Indonesia such as poverty, unemployment, economy, health and so on. Responding to population problems, state administrators are required to work harder starting from the central government to the related government level by collecting and ensuring the availability of accurate and complete population data as needed in order to fulfill population information. an approach that aims to describe the phenomena that occur in relation to the scope of the study. The data sources used in this study are data on people, places and paper and information retrieval through observation, interviews and documentation. The results of the study show that the implementation of SIAK carried out by the Population and Civil Registration Service of Southwest Sumba Regency is in accordance with applicable rules and policies, but in its implementation it still faces several problems. one of which is the lack of human resources and the lack of supporting facilities and infrastructure.